Testing the impacts of wildfire on hydrological and sediment response using the OpenLISEM model. Part 1: Calibration and evaluation for a burned Mediterranean forest catchment - Wu, Jinfeng (2021)
Models are typically applied to estimate the potential adverse effects of fire on land degradation and water resources and the potential benefits of post-wildfire rehabilitation treatments. However, few modeling studies have been conducted for meso-scale catchments, and only a fraction of these studies include transport and deposition of eroded material within the catchment or represent spatial erosion patterns. This study presents an application and evaluation of the OpenLISEM physically-based and spatially-distributed hydrological and soil erosion model for a burned Mediterranean meso-scale catchment (18.5 km2) in a data-scarce environment, using a robust parameterization and calibration procedure: (1) integrating satellite imagery and the topographic wetness index to support model parameterization; (2) event-based automated calibration using the Model-Independent Parameter Estimation and Uncertainty Analysis and parameters ensemble for before and after the fire; (3) a jack-knife cross-validation for model evaluation. The study shows that this procedure used in OpenLISEM provides reasonable results for pre- and post-wildfire catchment discharge and sediment transport (r2 and NSE > 0.5; absolute PBIAS < 25% for discharge and 55% for sediment transport). This may serve the needs of model applications in data-scarce burned areas. The results also provide recommended model parameters for burned areas with high severity such as random roughness (rr) = 2.41cm, and slope manning’s n (n) = 0.038; or post-wildfire to pre-wildfire ratios of model parameters such as saturated hydraulic conductivity (Ks) = 0.98×, channel manning’s n (chn) = 0.44×, grain size (d50) = 0.61×. The simulation results indicate that wildfire did not lead to significantly enhanced hydrological responses and soil erosion at the catchment outlet, partly explained by the spatial patterns of soil erosion. For both pre- and post-wildfire conditions, higher soil erosion was simulated in areas located far from the catchment outlet. The wildfire led to enhanced hillslope erosion, mostly in the upper part of the catchment, providing ample opportunities for transported sediment to deposit before reaching the outlet.